El enfrentamiento al cambio climático en la especialidad forestal de la educación técnica profesional - Capote Domínguez, Tania Esther; González Hernández, Gonzalo; Perdomo Ogando, Juan Manuel (My University, 2019)
La Universidad se encuentra frente a nuevos debates que llevan a cuestionar su verdadera función en la actualidad, debe considerarse uno de los agentes capaces de proporcionar formación avanzada, conocimiento y cultura a la población, cambio y transformación social, y mantener un equilibrio entre su misión, objetivos y demandas del Estado. Entre sus grandes tareas se presenta en la actualidad la introducción de la Tarea Vida. El Ministerio de Ciencia, Tecnología y Medio Ambiente, en su condición de Organismo de la Administración Central del Estado y rector de la política ambiental, es el encargado de proponer y controlar la estrategia, concertar las acciones encaminadas a mantener los logros ambientales alcanzados, contribuir a minimizar o eliminar las insuficiencias aún existentes y al mejoramiento constante de la calidad de vida de los ciudadanos.

The University is facing new debates that lead to questioning its true role at present, it should be considered one of the agents capable of providing advanced training, knowledge and culture to the population, change and social transformation, and maintain a balance between its mission, objectives and demands of the State. Among its major tasks is the introduction of the Life Task. The Ministry of Science, Technology and the Environment, in its capacity as an Organism of the Central State Administration and rector of environmental policy, is in charge of proposing and controlling the strategy, arranging actions aimed at maintaining environmental achievements, contributing to minimize or eliminate the still existing insufficiencies and to the constant improvement of the quality of life of the citizens. It is the responsibility of the university to prepare the teachers who teach the forestry specialty so that they can consciously and creatively introduce into their daily activities the confrontation with Climate Change in Cuba (Life Task), approved by the Council of Ministers in April. 2017, a system of improvement is proposed for these teachers in which debates, conferences and workshops that are linked through self-preparation are integrated; it is valued by the criterion method of specialists, with notable acceptance regarding its content, forms of organization, contextualization, relevance and applicability. The implementation shows its viability and the possibilities of achieving positive changes in personal and professional performance.
Facing the climate warming at the forestry specialty of the technical and professional school institutions
Keywords: Tarea Vida; Especialidad Forestal; Sistema de Superación; System of Improvement; Forestry Specialty; Life Task